Self-supported Zn3P2 nanowire arrays grafted on carbon fabrics as an advanced integrated anode for flexible lithium ion batteries. Issue 16 (6th April 2016) - Li, Wenwu; Gan, Lin; Guo, Kai; Ke, Linbo; Wei, Yaqing; Li, Huiqiao; Shen, Guozhen; Zhai, Tianyou
Abstract : The well-aligned binary lithium-reactive metal phosphide nanowire arrays were grafted on carbon fabrics. When served as integrated electrodes, they exhibit striking high initial coulombic efficiency, large capacity, excellent rate performance. Abstract : We, for the first time, successfully grafted well-aligned binary lithium-reactive zinc phosphide (Zn3 P2 ) nanowire arrays on carbon fabric cloth by a facile CVD method. When applied as a novel self-supported binder-free anode for lithium ion batteries (LIBs), the hierarchical three-dimensional (3D) integrated anode shows excellent electrochemical performances: a highly reversible initial lithium storage capacity of ca . 1200 mA h g −1 with a coulombic efficiency of up to 88%, a long lifespan of over 200 cycles without obvious decay, and a high rate capability of ca . 400 mA h g −1 capacity retention at an ultrahigh rate of 15 A g −1 . More interestingly, a flexible LIB full cell is assembled based on the as-synthesized integrated anode and the commercial LiFePO4 cathode, and shows striking lithium storage performances very close to the half cells: a large reversible capacity over 1000 mA h g −1, a long cycle life of over 200 cycles without obvious decay, and an ultrahigh rate performance of ca . 300 mA h g −1 even at 20 A g −1 . Considering the excellent lithium storage performances of coin-type half cells as well as flexible full cells, the as-prepared carbon cloth grafted well-aligned Zn3 P2 nanowire arrays would be a promising integrated anode for flexible LIB full cell devices.